Sleep and Behavior in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
Potential relationships between objectively measured sleep disturbances and neurobehavioral function in a community cohort of 5- to 7-year old children with parentally reported symptoms of ADHD were investigated at the University of Louisville, KY.